Delayed sleep-wake rhythm due to staying at home during the COVID-19 pandemic and sleep debt after returning to campus among Japanese nursing university students: A longitudinal study. Issue 4 (April 2023) - Kayaba, Momoko; Ishitsuka, Mami; Ishidate, Miyako; Ueno, Kimiko; Kajihara, Yoko; Sasai-Sakuma, Taeko
Abstract: This study aimed to investigate sleep problems during staying at home due to the coronavirus disease 2019 (COVID-19) pandemic and after returning to campus among university nursing students. We analyzed data from self-reported sleep surveys conducted during a nursing course at a university in Tokyo between 2019 and 2021. During staying at home due to COVID-19, we observed delayed sleep-wake rhythm, prolonged sleep duration on weekdays, a decreased sleep debt, improved daytime sleepiness, and worsened insomnia, especially in terms of difficulty initiating sleep (Study 1; 18 paired data). After returning to campus, we found advanced wake-up time, shortened sleep duration, increased sleep debt, worsened insomnia, and increased daytime sleepiness (Study 2; 91 paired data). The association between advanced midpoint of sleep and commute time over an hour (aOR, 3.29; 95%CI: 1.24–8.72) was confirmed. Furthermore, sleep paralysis and nightmares were more prevalent among nursing students with an advanced midpoint of sleep, whereas nursing students whose midpoint of sleep was delayed had higher daytime sleepiness after returning to campus. To maintain regular sleep-wake rhythms and sufficient sleep duration, the educational environment surrounding nursing university students (e.g., curriculum, class schedule, style of class) should be established considering their age-dependent biological rhythm in addition to sleep hygiene education for students.